Development of an Anti-Acne Facial Wash Gel With Cassia alata L. Leaf Extract - Meirista, Indri; Mariska, Ruri Putri; Jannah, Miftahul (Jurnal Kesehatan, 2024)
Acne is a skin disease that is often encountered. Acne can be caused by various factors, including bacterial infection. To prevent acne, keep facial skin clean using facial wash. Using facial wash made from synthetic substances can cause more significant side effects than natural ingredients, so research is needed on natural ingredients that can be used as anti-acne agents. One natural ingredient that has antibacterial activity is ketepeng leaf (Cassia alata L.). This research aims to formulate a facial wash gel preparation from ketepeng leaf extract and test its antibacterial activity against Staphylococcus aureus bacteria. This research is experimental research starting from making extracts, dosage formulation, evaluating the physical properties of the dosage (stability test, organoleptic test, homogeneity test, pH test, viscosity test, spreadability test, and foamability test), skin irritation test, hedonic test and antibacterial activity against Staphylococcus aureus bacteria. The research results showed that the inhibition zone produced by formula 1 was 9.73mm, formula 2 was 10.33mm, and formula 3 was 13.18mm. This research concludes that Ketepeng leaf can be used as an active ingredient in anti-acne facial wash gel preparations because the Ketepeng leaf extract facial wash gel preparation meets the requirements for evaluating good physical properties and has antibacterial activity against Staphylococcus aureus bacteria in each formula.